IPad the missing manual - Pogue, David 1963- (O'Reilly Media, Inc., 2014)
Annotation
Includes index. - Online resource; title from PDF title page (EBSCO; viewed on December 18, 2014)
Keywords: Tablet computers -- Handbooks, manuals, etc; iPad (Computer) -- Handbooks, manuals, etc; Tablettes électroniques; Guides, manuels, etc; iPad (Ordinateur); Guides, manuels, etc; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; iPad (Computer); Tablet computers; handbooks; Handbooks and manuals; Guides et manuels